SUBSTRATES AND LIGHT CONDITIONS IN THE GROWTH OF SEEDLINGS OF Parkia multijuga BENTH. - Maekawa, Luiz; Coelho, Maria de Fatima Barbosa (Floresta, 2021)
The forest species Parkia multijuca Benth. occurs in the Northwest Region of Mato Grosso State, Brazilian Amazon region, important for the recovery of degraded areas of permanent preservation, mainly due to its rapid growth. The aim of this study was to identify the best combinations of substrates and light conditions for the development of Parkia multijuga seedlings in nursery. The experimental design was in randomized blocks, arranged in a plot scheme subdivided 4 x 11, with four replications. The light conditions were full sun, 30%, 50% and 70% shading. The substrates were: 1 - Soil; 2 - Soil + limestone "filler"; 3 - Soil + limestone + cattle manure; 4 - Soil + limestone + simple superphosphate; 5 - Soil + limestone + simple superphosphate + catlle manure; 6 - Solo + thermophosphate and 7 - Soil + thermophosphate + bokashi. The morphological parameters used were shoot height, diameter, number of leaves, total dry mass, shoot mass, dry mass of roots, relationship between height and diameter, height and dry shoot mass, between dry shoot mass and root dry mass, and the Dickson quality index (IQD). The seedlings of Parkia multijuga can be produced in a nursery with higher quality in full sun and in substrate with 25% cattle manure. Shading should not be used in the production of Parkia multijuga seedlings.